Continuous Pleural Infusion of Bupivacaine Offers Better Postoperative Pain Relief than Does Bolus Administration. Issue 1 (January 1992) - Aguilar, Jose Luis; Montero, Antonio; F-Llamazares, Jaime; Montes, Antonio; Vidal, Fernando; Pastor, Cruz
Abstract : Background and Objectives: To determine whether continuous pleural analgesia offers better postoperative pain relief than does bolus administration in postcholecystectomy patients. Methods: Eighty postcholecystectomy patients with a subcostal incision were randomly allocated to receive pleural analgesia with either a bolus regime of 20 ml 0.375% bupivacaine with 1:200, 000 epinephrine at four-hour intervals (bolus group), or a loading dose of 20 ml 0.375% bupivacaine with 1:200, 000 epinephrine immediately followed by a continuous infusion at a rate of 6 ml/hour during the first 24 hours postoperatively (infusion group). A 10-cm linear visual analog scale was used and recorded before performing pleural analgesia and at 1, 6, 12, 18, and 24 hours subsequently. Plasma levels of bupivacaine were determined in eight patients of the infusion group. Samples were taken at 5, 15, 30, and 60 minutes and at 6 and 18 hours after the start of infusion. Results: Mean visual analog scale values were significantly lower ( p < 0.001) at 6, 12, 18, and 24 hours in the infusion group. PaCO2 decreased significantly ( p <0.001) after the block in both groups, with no difference between the groups. Plasma levels were well below toxic levels in the infusion group. Conclusions: Continuous pleural analgesia offers better postoperative pain relief than does bolus administration. Pneumothorax was observed in two patients during the study.